EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS DEEP LEARNING DI SEKOLAH MENENGAH PERTAMA - Danu Niti Baskara; Falahudin; Fitri Hilmiyati; Enung Nugraha (STKIP Subang, 2026)
This study aims to analyze the implementation of Deep Learning-based evaluation in Islamic Religious Education (PAI) at the junior high school level within the framework of the Merdeka Curriculum. Employing a descriptive qualitative approach, data were collected through classroom observation, in-depth interviews, and document analysis involving Islamic education teachers, students, and school administrators. The findings reveal that the principles of Deep Learning have been incorporated into PAI learning through reflective, contextual, and spiritually grounded activities. Teachers act not only as instructors but also as reflective facilitators who guide students to comprehend, internalize, and apply Islamic values in their daily lives. The evaluation process has shifted from traditional assessment toward authentic assessment, such as reflective journals, religious practice projects, and behavioral observations. However, the affective and spiritual aspects of learning assessment remain underdeveloped due to limited instruments and teachers’ lack of understanding of holistic evaluation. This study recommends continuous professional development programs for Islamic education teachers to enhance their competence in designing value-based and spiritually oriented assessment tools. The implementation of Deep Learning in PAI learning is expected to strengthen students’ religious awareness, Islamic character, and spiritual intelligence in a comprehensive and sustainable manner.